Analysis and Evaluation of Nutrient Components in Petals of Different Dahlia Varieties - Zhen LIU; Lu WANG; Lulei CAO; Shance NIU; Diying XIANG; Duanfen CHEN; Wenbin YU; Lihong HAO (Shipin gongye ke-ji, 2023)
Comparison of differences in the nutritional quality of different dahlia varieties could facilitate the selection of varieties with excellent nutritional quality. This would provide a basis for the resource evaluation and deployment of dahlia. In this study, this study determined the nutrition components in petals of 36 dahlia varieties at the complete flowering stage including soluble sugar, soluble protein, vitamin C, organic acid, anthocyanin, total phenol, flavonoid, and DPPH free radical scavenging rate. This study also examined the correlation between these indexes. In addition, the nutritional quality indexes of each variety were comprehensively analyzed using principal component analysis and cluster analysis. This study revealed that many Dahlia cultivars had significant differences in component content. The coefficient of variation of vitamin C content and coefficient of variation of organic acid content was the highest (51.94%) and the lowest (7.92%), respectively. The contents of soluble sugar, soluble protein, vitamin C, and organic acid in different varieties of dahlia ranged from 6.95 to 15.57 mg/g, 0.96 to 2.01 mg/g, 1.20 to 151.37 mg/100 g, and 0.38% to 1.10%, respectively. The total phenol content and anthocyanin content of active substances were 0.19 to 0.25 mg/g and 0.61 to 2.51 mg/g, respectively. The flavonoid content was 0.54 to 4.81 mg/g and the DPPH free radical scavenging rate was 0.12% to 0.67%. The correlation analysis showed that the eight indexes were largely correlated. Principal component analysis was used to extract five principal components and the cumulative variance contribution rate reached 81.39%. These findings suggested that a detailed analysis of soluble sugar, vitamin C, anthocyanin, organic acids, flavonoids, and DPPH free radical scavenging rate can be used as core indicators to evaluate the nutritional quality of dahlia. According to cluster analysis, 36 dahlia varieties can be grouped into five categories. This study shows that YH-C7 and YH-C4 had the best nutritional quality.